Improving Students’ Writing through Genre Based Approach at SMP Negeri 7 Kota Ternate - Aprilisa R. Taher; Silvani Umar Ali; Indry Widyasti Anwar (EDU Journal - English Department of UMMU Journal, 2023)
Abstract: The purpose of this research was to find out whether the teaching of recount text through a genre-based approach can improve students’ ability to write recount text. This research was conducted on students of class VIII-H at SMP Negeri 7 Kota Ternate. This study used quantitative methods in collecting and analyzing data. The number of research samples were 20 students of class VIII H selected through simple random sampling technique. The instrument used in this study were pre-test and post-test to collect data. The researcher analyzed the students’ writing on the pre-test, the first cycle test and the second cycle test. To evaluate students’ results in writing recount text, the researcher used a writing rubric The results showed that the average score of the students on the first test was 53 and the average score on the second cycle test was 73.75, the results of the t-test (12) exceeded the t-value (1.729) at a significant level of 0.05 and degrees of freedom (19) using one tiled test. Therefore, the alternative hypothesis (Hi) is accepted while the null hypothesis (H0) is rejected. It was concluded that there were differences between students who wrote recount text during the pre-test, and after applying the genre-based approach during the post- test.